Sustainable Business Practices Supporting SDGs Across ASEAN Economies - Agus Rohmat Hidayat; Nur Alifah; Kyra Kholilah Wardaniyah (Jurnal Syntax Admiration, 2026)
This study examines the role of sustainable business practices in advancing the United Nations Sustainable Development Goals (SDGs) across ASEAN economies. Drawing on a systematic review of recent empirical literature and secondary data from 10 ASEAN member states for the period 2015–2023, the study evaluates how environmental, social, and governance (ESG) frameworks, green investments, renewable energy consumption, circular economy strategies, creative economy, and human resource management (HRM) contribute to SDG attainment. Using a Composite Sustainability Index (CSI) and panel regression analysis, the findings reveal that ASEAN countries achieving higher ESG alignment scores demonstrate significantly greater progress toward SDG targets, with a mean CSI score of 62.4 out of 100 as of 2023. The results further indicate that renewable energy adoption and green economic growth are the strongest predictors of sustainability performance (β = 0.47, p < 0.001), while governance quality and corporate ESG disclosure amplify these effects. Sectoral analysis highlights heterogeneity in SDG progress, with the manufacturing and logistics sectors lagging relative to the services and technology sectors. The study contributes to the theoretical understanding of sustainable business-SDG linkages in developing regional economies and offers actionable policy recommendations for ASEAN governments and corporate actors.